Effect of Pilocarpine Mouthwash on Salivary Flow Rate in Patients with Xerostomia: A Systematic Review and Meta-Analysis - Katayoun Katebi; Shirin Hassanpour; Hosein Eslami; Fatemeh Salehnia; Hossein Hosseinifard (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: Xerostomia is a subjective sensation of dry mouth considered as a complex state affecting multiple oral functions. Pilocarpine may be a useful medication for the treatment of xerostomia, but its side effects limit its use under certain conditions. Recent studies have focused on the pilocarpine mouthwash as an alternative. Purpose: We have undertaken this study to review the latest available scientific evidence systematically, concerning the effects of pilocarpine mouthwash on salivary flow rate in patients with xerostomia. Materials and Method: An electronic search for randomized controlled trials published in English until September 2021 related to pilocarpine mouthwash and salivary flow rate in patients with dry mouth was performed in PubMed/Medline, Web of Science, Google Scholar, Embase, and Scopus. A random-effects meta-analysis was conducted to evaluate the relationship between the groups. Results: Two papers with 86 patients were selected for the final review based on strict eligibility criteria. According to the results of the meta-analysis, the mean visual analogue scale in the patient treated with pilocarpine mouthwash was 0.88 unit lower than that of the control group in the fourth week follow; however, it was not statistically significant (pooled mean difference=-0.88, 95% CI = (-2.72; 0.95), p= 0.34). Conclusion: It seems that the use of pilocarpine mouthwash can increase the salivary flow rates; however, no optimal dose and application regimen can currently be suggested due to the high heterogeneity of the data. Regarding the relief of the symptoms using pilocarpine mouthwash, the existing evidence does not support its effectiveness.